The Role of Sonic Hedgehog Pathway in the Development of the Central Nervous System and Aging-Related Neurodegenerative Diseases - Yang, Chen; Qi, Yan; Sun, Zhitang (Frontiers in Molecular Biosciences, 2021)
Sonic hedgehog (SHH) pathway affects neurogenesis and neural patterning during the development of central nervous system. Dysregulation of SHH pathway in brain contributes to aging-related neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. At present, SHH signaling pathway can be divided into canonical signaling pathway and non-canonical signaling pathway, which directly or indirectly mediates other related pathways involved in the development of neurodegenerative disease. Hence, an in-depth knowledge of SHH signaling pathway may open an avenue of possibilities for the treatment of neurodegenerative disease. Here, we summarize the role and mechanism of SHH signaling pathway in the development of the central nervous system and aging-related neurodegenerative disease. In this review, we will also highlight the potential of SHH pathway as a therapeutic target for treating neurodegenerative disease.